(untitled) (University of Khartoum Engineering Journal, 2022)
The objective of this study is to provide rheological data of Acacia senegal (A. senegal) gum of Kordofan origin. The density of A. senegal gum at room temperature is found to be higher than that of water only at higher concentration (>5 g/L). The density is aslo found to be strong function of temperature. At medium temperature >45 °C becomes lower than that of water even at low concentration (<2.5 g/L). The viscosity is found to be shear rate independent indicating Newtonian behavior. At low concentration A. senegal gum viscosity varies linearly with concentration and at high concentration (>10 g/L) varies exponentially. The study also provides review information on physicochemical and mineralogical characteristics as well as the structure of A. senegal gum.